Stability Evaluation and Mechanism of Asphalts Modified With Various Rubber Powder Contents - Xue, Hengxiao; Cao, Yuanbo; Liu, Qi; Zhang, Hongfei; Zhang, Mingliang (Frontiers in Materials, 2021)
Ground tires are one of the main sources of urban solid waste. Rubber powder-modified asphalt provides an effective method to solve the problem, and it presents good high- and low-temperature performance in sustainable pavement construction. However, the storage properties of rubber powder-modified asphalts prepared from the traditional low-temperature shear mixing method are unstable, which restricts their application. In this study, four test methods (the softening-point test; the dynamic shear rheological, DSR, test; the Laboratory Asphalt Stability Test, LAST; and fluorescence image analysis) and six evaluation indexes (the softening-point difference Sdiff, the segregation percentage Sp, the segregation index Ise, the segregation rate Rs, the degradation rate Rd, and the stability index Ist) were employed to analyze the storage abilities of asphalts modified by various activated rubber powder contents. The results show that the storage properties have a positive correlation with rubber powder content in the modified asphalt, and a rubber powder content of 60% is proven to be the optimum mixing amount. The rubber powders can distribute uniformly in the asphalt matrix when mixed below the optimum mixing amount, otherwise a rubber-powder agglomeration is formed. The quantitative morphology analysis results are in good agreement with the laboratory test conclusions. The activated rubber powder shows better compatibility compared with ordinary rubber powders and presents a promising method to treat waste ground tires.